Pengaruh Digital Marketing dan e-wom terhadap Keputusan Pembelian Produk Skincare Ms Glow (Survei pada Pelanggan Store Ms Glow Sukabumi) - Nuraidah Nuraidah; Liya Megawati (Jurnal Ilmiah Wahana Pendidikan, 2023)
This study aims to identify, analyze and explain how the description, correlation, partial effect and simultaneous influence of Digital Marketing and E-WOM on the Purchase Decision of MS Glow Skincare Products (Survey on MS Glow Sukabumi Store Customers) uses quantitative methods with descriptive and verification approaches. With a sample of 302 respondents taken from the customer population of the Ninda MS Glow Sukabumi Store, a total of 1,409 consumers in the 2022 period using a non-probability sampling technique. As well as using path analysis and hypothesis testing using the t test and f test. By using Microsoft Excel tools, Method of Successive Interval (MSI), and the SPSS application version 25. Based on the results of the analysis that has been carried out, this study proves that the description of Digital Marketing, E-WOM and the decision to purchase MS Glow Sukabumi skincare products are in the good category. Digital Marketing variable with an average score of 1,272.8 out of a maximum score of 1,510, E-WOM variable with an average score of 1,282 out of a maximum score of 1,510, Purchase Decision variable with an average score of 1,223 out of a maximum score of 1,510. The correlation coefficient between the variables Electronic Word of Mouth and Advertising Through YouTube obtained a value of 0.786 which means it has a strong, positive and significant correlation level between Digital Marketing and E-WOM. The partial effect of Digital Marketing on Purchase Decisions is 23%, while the partial effect of E-WOM on Purchase Decisions is 23.5%. So it can be stated that E-WOM has a greater contribution to Purchase Decisions compared to Digital Marketing. The simultaneous effect of Digital Marketing and E-WOM on Purchasing Decisions is 46.5% while the remaining 53.5% is another variable not examined in this study.